2020
DOI: 10.1007/s00421-020-04375-9
|View full text |Cite
|
Sign up to set email alerts
|

Acute hypertrophic but not maximal strength loading transiently enhances the kynurenine pathway towards kynurenic acid

Abstract: Purpose Due to distinct immuno-and neuro-modulatory properties, growing research interest focuses on exercise-induced alterations of the kynurenine (KYN) pathway in healthy and clinical populations. To date, knowledge about the impact of different acute strength exercise modalities on the KYN pathway is scarce. Therefore, we investigated the acute effects of hypertrophic (HYP) compared to maximal (MAX) strength loadings on the KYN pathway regulation. Methods Blood samples of twelve healthy males (mean age and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 21 publications
(30 reference statements)
0
19
0
Order By: Relevance
“…23,40,43 One study showed an acute effect of high intensity exercise in healthy subjects, resulting in increased KYNA directly after exercise and then back to baseline after 1 hour. 45 Endurance training also increases plasma QUIN levels, 22,23,43 while resistance exercise does not. 23,43 It is clear from these works that the type of exercise (endurance, resistance or nonendurance) and baseline fitness levels (eg, someone running a marathon 22 or cycling long-distances 43 is well-trained to perform that task) differentially influence metabolism along the kynurenine pathway.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…23,40,43 One study showed an acute effect of high intensity exercise in healthy subjects, resulting in increased KYNA directly after exercise and then back to baseline after 1 hour. 45 Endurance training also increases plasma QUIN levels, 22,23,43 while resistance exercise does not. 23,43 It is clear from these works that the type of exercise (endurance, resistance or nonendurance) and baseline fitness levels (eg, someone running a marathon 22 or cycling long-distances 43 is well-trained to perform that task) differentially influence metabolism along the kynurenine pathway.…”
Section: Discussionmentioning
confidence: 98%
“…For instance, in healthy subjects, exercise intensity affects the kynurenine metabolites differently, by increasing KYNA plasma levels after hypertrophic strength loading, but not after maximal strength loading. 45 Irrespective of lab-to-lab variations in methods and design, together, these sometimes-contradictory studies suggest that plasma kynurenine metabolites can change within temporally limited windows and that the direction of change depends on the type, length and intensity of the exercise performed. The current investigation also presents some limitations with respect to the experimental design such as lack of physiological parameters controlling for “all-out” performance and uncontrolled food intake before plasma sampling.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13][14] Most of these studies investigated severe aerobic exercise as intervention in the form of an incremental exercise test until exhaustion. [11][12][13][14] Furthermore, several studies reported an increased metabolic flux towards KA following acute exercise, 10,[15][16][17] which could possibly be due to an elevation in KAT enzyme expression. Not only the metabolic flux towards KA, but also the major branch of the KYN pathway towards QA can apparently be upregulated after acute exercise.…”
Section: Physical Exercise As Kynurenine Pathway Modulator In Chronicmentioning
confidence: 99%
“…Recent results suggest that alterations of KYN pathway metabolites measured in blood serum are of transient nature, and levels return to baseline within 1 hour after exercise cessation. 10,15 Regarding the effects of chronic exercise training on the KYN pathway, existing evidence from human studies is more contradictive compared with effects of acute exercise. Many studies do not show statistical effects on circulating metabolites, [19][20][21] but the design and/or description of the interventions is questionable due to low training frequency/ intensity or lacking information on the applied exercise modalities and adherence.…”
Section: Physical Exercise As Kynurenine Pathway Modulator In Chronicmentioning
confidence: 99%
See 1 more Smart Citation